PELAKSANAAN PERJANJIAN KERJASAMA PROGRAM SANITASI MASYARAKAT DI KOTA PEKANBARU - Akbar, Muhammad Fauzi; Ismi, Hayatul; Firmanda, Hengki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In the development of this Community Sanitation Program, the Pekanbaru City government through its Work Unit entered into an agreement with the Community Self-Reliance Institution. This is stated in the Collaboration Agreement for the Community-Based Sanitation Program of 2017 Number 09 / SPKS / SANIMAS-IDB / PIP-PKU / VII / 2017 on July 5, 2017. However, in its implementation there have been various problems related to the rights and obligations carried out by the two defenses. the promised party. Therefore, this study aims to: find out the rights and obligations of the parties based on the Cooperation Agreement for the Community Sanitation Program in Pekanbaru City. As well as obstacles and efforts to resolve defaults in the Community Sanitation Program Cooperation Agreement in Pekanbaru City. The method used in writing this research is a qualitative approach, with 2 key informantsThe results of this study indicate that: 1) The government through the work unit has fulfilled its obligations to make project payments, and the MFI has received the right and fulfilled its obligations. However, the implementation of the obligations (the construction of WWTP in Kelurahan Cahaya Limbungan) is still not in accordance with the agreement, especially in relation to the processing time and also the location of the construction. 2) the obstacles faced in fulfilling the rights and obligations are related to the project execution time. the government only pays for projects in accordance with the progress of physical development. Therefore, the settlement of this default is that the government provides a grace period for the MFI to complete the project, without any additional costs from the governmentIt can be concluded that there were problems in the field, in which the parties did not carry out their obligations properly which triggered defaults. It is better if the parties who are bound by the agreement can carry out what they have promised so that there is no problem in the field..Keywords: Agreement, Cooperation, Default.